2022
DOI: 10.1111/jfpp.16631
|View full text |Cite
|
Sign up to set email alerts
|

Study on the antifungal mechanism of Chinese herbal extract on Botryosphaeria dothidea

Abstract: Kiwifruit (Actinidia chinensis Planch) is a perennial deciduous vines (Tilahun et al., 2019). Its unique flavor and abundant nutrients, such as high levels of vitamin C, anthocyanins, flavone, dietary fiber, and amino acids (Drevinskas et al., 2017;Liu et al., 2019). It has high edible value and health benefits, including hypolipidemic, cholesterol-lowering, antioxidant and cosmetic properties, etc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…This is consistent with the antifungal mechanism of the Eriobotrya japonica leaf extract and the Chinese herbal extract compound (CHEC) on MDA. 67,68 The destruction of the cell membrane was also confirmed through the phenomenon of the mycelium being transparent and ruined by light microscopy. In the meantime, according to the increased transparency and breaking of the mycelium, we speculate that the petroleum ether extract may also do harm to the cell wall.…”
Section: ■ Discussionmentioning
confidence: 85%
“…This is consistent with the antifungal mechanism of the Eriobotrya japonica leaf extract and the Chinese herbal extract compound (CHEC) on MDA. 67,68 The destruction of the cell membrane was also confirmed through the phenomenon of the mycelium being transparent and ruined by light microscopy. In the meantime, according to the increased transparency and breaking of the mycelium, we speculate that the petroleum ether extract may also do harm to the cell wall.…”
Section: ■ Discussionmentioning
confidence: 85%
“…Nevertheless, it can be observed that G. lucidum -based treatments exhibit some of the highest activities against the four phytopathogens. Regarding B. dothidea , the efficacy of the pure extract is comparable to that of a compound herbal extract compound consisting of seven Chinese medicinal plants [ 60 ]. Meanwhile, the activity of the conjugate complex is intermediate between those of COS- U. dioica and COS- E. arvense conjugates [ 41 ], tested against the same isolate.…”
Section: Discussionmentioning
confidence: 99%
“…DPPH scavenging capacity and SOD activity reflect antioxidant activities, which are associated with fungal adaptability to different environmental and stress conditions and host-infection ability [ 46 ]. Besides SOD, Shi et al [ 47 ] found that preservative treatment can reduce enzyme activities, including CAT, POD, NADP-malate dehydrogenase, succinate dehydrogenase, cellulase, and glucanase, in Bot. dothidea .…”
Section: Discussionmentioning
confidence: 99%